The Impact of the Application of the Time-Driven Cost System (TDABC) on the Quality of Administrative Decisions - Case Study - Israa University - Abourahma, Mohamed Abdelah; Hamed, Khaled Youcef (Finance and Business Economies Review, 2019)
The Study aimed to know the impact of The Time Driven Activity Based Costing (TDABC) to identify the impact of the implementation of the Time Management System (TDABC) at the Israa University on providing information that contributes to quality management decisions, reducing costs and enhancing oversight role. A survey list was used for this purpose, (42) companies. The deans of the college, their deputies, directors and heads of the administrative and financial departments were chosen. The study followed the descriptive analytical method, The study found that the impact of the implementation of the Time Management System (TDABC) at the University College of Science and Technologyprovides accurate information that contributes to quality management decisions, helps to reduce costs, enhance oversight and provide quality service. In light of these results, the study presented a number of recommendations, the most important of which are: To sensitize the higher management institutions, whether educational, service or industrial, to the importance of adopting and applying modern administrative accounting methods, especially the (TDABC) system in response to rapid environmental changes that are becoming increasingly complex day after day.